2013
DOI: 10.1007/s12350-013-9710-6
|View full text |Cite
|
Sign up to set email alerts
|

A hypothetical protocol for the provisional use of perfusion imaging with exercise stress testing

Abstract: A provisional injection protocol defined as age < 65, normal rest ECG, no history of CAD, and high level exercise with a negative ECG response and no symptoms has a very low 5-year all-cause mortality and low yield of MPI. If adopted it would decrease radiation exposure and save time and health care costs without jeopardizing prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…In this issue of the journal, Duvall et al, 10 recognizing that the results of MPI seemed to add little to risk assessment of patients who exercise to 10 METs or more during stress testing, seek to determine if a provisional tracer injection protocol could be developed in which a patient would not have the tracer administered intravenously if C10 METs was achieved without symptoms and with a negative stress ECG response. They retrospectively reviewed all patients who underwent a SPECT MPI study over a 6.5-year period and estimated how many patients might have been eligible for a ''standby injection'' protocol with provisional MPI.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of the journal, Duvall et al, 10 recognizing that the results of MPI seemed to add little to risk assessment of patients who exercise to 10 METs or more during stress testing, seek to determine if a provisional tracer injection protocol could be developed in which a patient would not have the tracer administered intravenously if C10 METs was achieved without symptoms and with a negative stress ECG response. They retrospectively reviewed all patients who underwent a SPECT MPI study over a 6.5-year period and estimated how many patients might have been eligible for a ''standby injection'' protocol with provisional MPI.…”
mentioning
confidence: 99%
“…The number of patients who might not have been injected with tracer for MPI could have been expanded if Duvall et al 10 did not include shortness of breath as an endpoint or included patients with an intermediate pretest likelihood of CAD who were [65 years of age. Patients were withdrawn from the provisional imaging protocol if they had right bundle branch block on their resting ECG.…”
mentioning
confidence: 99%
“…ETT is an even faster diagnostic test for the low-risk patient and a provisional isotope injection protocol might provide the time savings of ETT with the flexibility of imaging when needed. 38 More progress can and has been made at reducing patient radiation exposure with both CTA and SPECT MPI since 2011. CTA has made great strides in a short period of time through software, hardware, and protocol advances.…”
Section: 6mentioning
confidence: 99%
“…44,45 The use of time imaging software which incorporates iterative image reconstruction with resolution recovery thereby improving count statistics can decrease imaging time or decrease injected activity. 46 Stress protocol changes such as performing more ETTs, 47 developing a provisional isotope injection protocol, 38 and stress-first imaging 10 will all decrease radiation exposure to the patient by not giving it in the first place. Perhaps the greatest saving of radiation exposure and resources would be the elimination of any diagnostic testing for most of the very low-and low-risk patients (''less is more'').…”
Section: 6mentioning
confidence: 99%
“…28 Thus, the relationship among METS, stress-induced ischemia, and prognosis in diabetic subjects remains unclear. In another recent study, Duvall et al 29 showed that a provisional injection protocol defined as age \65, normal rest ECG, no history of CAD, and high level exercise (C10 METS) with a negative ECG response and no symptoms has a very low 5-year all-cause mortality and low yield of MPS. If adopted, this protocol would decrease radiation exposure and save time and health care costs without jeopardizing prognosis.…”
Section: Prognostic Value Of Exercise Level In Diabetic Patientsmentioning
confidence: 99%